The role of the near-surface pathways in the delivery of flow and nutrients to streams in Irish catchments - Deakin, Jenny (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2014)
Management of pollution from diffuse agricultural and small point sources remains a significant challenge worldwide. Understanding and quantifying the contributions of flow and nutrients, through each hydro(geo)logical pathway, to the receptor of interest, is an important part of identifying the highest-risk, critical source areas (CSAs). The aim of this research was to develop an improved conceptual understanding of the near-surface pathways in the delivery of flow and nutrients to streams. The near-surface pathways included interflow, artificial drainage and flow in the transition zone, i.e. the weathered zone between the top of the bedrock and the overlying subsoils.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin